Content Analysis of Psychological Posts during Covid-19 Outbreak in Cyberspace - Younesy Maleh, Masoumeh; Mirhashemi, Malek; Kord, Bahman; Bagheri, Nasrin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: The outbreak of Covid-19 has had a variety of psychological effects on people around the world. Despite the prosperity of cyberspace in this period, it is important to study the psychological posts of people in this space. This study aimed to explain and classify psychological posts during the outbreak of Covid-19. Method: The method of this qualitative study was contractual and directional text content analysis which was performed by the Shannon entropy method in the period of June 2016 to March 2017. The study population included all psychological posts on social media about the Covid-19 during the outbreak of the virus. Due to the qualitative nature of this study, based on the theoretical saturation rule and according to the opinion of experts in this field, 223 posts with a psychological theme were purposefully selected and examined. Then the classes and subclasses were analyzed manually. Results: Psychological posts during the outbreak of Covid-19 can be divided into two main categories: psychological well-being and psychological pathology. Psychological well-being has subcategories of lifestyles and skills, positivity, meaning and purpose, social support, and gratitude. Psychopathology also has three subcategories: externalization and internalization, psycho-behavioral problems, and defense mechanisms. Moreover, each of the subcategories has second-row subcategories through which the subcategories are identified and distinguished. Conclusion: The various psychological and non-psychological posts presented during the Covid-19 outbreak need further study. Therefore, it is suggested that in future studies, psychological posts be considered about mental illness.